The Fabrication of Banana Slicer, supervised - Dodi Mowo Asmoro; Saipul Bahri Daulay; Ainun Rohana (Universitas Sumatera Utara, 2013)
The manufacturing process of agricultural crops into a foodstuff is an interesting thing to be known. It appeared that many agricultural crops that have been processed further become more economics value than before. One of the fabricated processes is slicing. The aim of this research was to design, build, and test the fabricated banana slicer, conducted in November 2011 to April 2012 at the Laboratory of Agriculture Engineering, Faculty of Agriculture, University of Sumatera Utara, Medan, by literature study, experiment, observation, and testing of the equipment. The parameters observed were effective capacity and percentage of unsliced material. The result of the research showed that the effective capacity of the equipment was 24,25 kg/hr with 16,67% unsliced materials.